Rapid disc settling and the transition from bursty to steady star formation in Milky Way-mass galaxies. Issue 2 (23rd December 2022) - Gurvich, Alexander B; Stern, Jonathan; Faucher-Giguère, Claude-André; Hopkins, Philip F; Wetzel, Andrew; Moreno, Jorge; Hayward, Christopher C; Richings, Alexander J; Hafen, Zachary
ABSTRACT: Recent observations and simulations indicate substantial evolution in the properties of galaxies with time, wherein rotationally supported and steady thin discs (like those frequently observed in the local Universe) emerge from galaxies that are clumpy, irregular, and have bursty star formation rates (SFRs). To better understand the progenitors of local disc galaxies, we carry out an analysis of three FIRE-2 simulated galaxies with a mass similar to the Milky Way at redshift z = 0. We show that all three galaxies transition from bursty to steady SFRs at a redshift between z = 0.5 and z = 0.8, and that this transition coincides with the rapid (≲1 Gyr) emergence of a rotationally supported interstellar medium (ISM). In the late phase with steady SFR, the rotational energy comprises 90 per cent of the total kinetic + thermal energy in the ISM, and is roughly half the gravitational energy. By contrast, during the early bursty phase, the ISM initially has a quasi-spheroidal morphology and its energetics are dominated by quasi-isotropic in- and outflows out of virial equilibrium. The subdominance of rotational support and out-of-equilibrium conditions at early times challenge the application of standard equilibrium disc models to high-redshift progenitors of Milky Way-like galaxies. We further find that the formation of a rotationally-supported ISM coincides with the onset of a thermal pressure supported inner circumgalactic medium (CGM). Before this transition, there is no clear boundary between the ISM and the inner CGM.